1996
DOI: 10.1093/clinids/23.3.577
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Disease: Clinical Features, Serotypes, and Antimicrobial Resistance Patterns in Cases Involving Patients with and Without Human Immunodeficiency Virus Infection

Abstract: We reviewed 153 episodes of invasive pneumococcal disease involving 147 hospitalized patients with and without human immunodeficiency virus (HIV) disease to examine and compare epidemiologic and clinical features, capsular serotypes, and antibiotic susceptibility patterns. HIV infection was the most common risk factor for invasive pneumococcal disease. Pneumococcal disease in HIV-infected individuals was characterized by the greater frequency with which pneumonia was the source of bacteremia (90% vs. 63%) (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 63 publications
3
49
0
8
Order By: Relevance
“…HIV-infected individuals have a 6-to 324-fold-higer risk of invasive pneumococcal infections (34,111,162). Highly active antiretroviral therapy (HAART) reduces this risk but leaves it 35 times higher than that for meningitis patients without HIV infection (34,130,143).…”
Section: Immunocompromised Statementioning
confidence: 99%
“…HIV-infected individuals have a 6-to 324-fold-higer risk of invasive pneumococcal infections (34,111,162). Highly active antiretroviral therapy (HAART) reduces this risk but leaves it 35 times higher than that for meningitis patients without HIV infection (34,130,143).…”
Section: Immunocompromised Statementioning
confidence: 99%
“…In South Africa, 83% of serotypes incriminated in HIV-seropositive children were included in the nine-valent conjuguated pneumococcal vaccine [27]. Finally, in the USA, FRANKEL et al [28] also found that 90% of the serotypes responsible for invasive pneumococcal disease, particularly serotypes 9, 14, 6b and 22 f, were equally included in the polyvalent pneumococcal vaccine.…”
Section: Bacteria Responsible For Lower Respiratory Tract Infectionmentioning
confidence: 99%
“…[12,13] With the HIV epidemic and the worldwide emergence of drug-resistant pneumococci, the incidence of invasive pneumococcal disease has increased. [14] Invasive pneumococcal disease (IPD) has been described to affect almost every organ and thus the clinical manifestations and outcomes of the disease vary tremendously. [15,16] Among risk factors, older age (65 years) and immunocompromised state are notably associated with higher incidence of the invasive disease and increased mortality rates.…”
Section: Discussionmentioning
confidence: 99%